Development of molecularly imprinted polymer based solid phase extraction sorbents for the selective cleanup of food and pharmaceutical residue samples - Batlokwa, Bareki Shima (Rhodes University, Faculty of Science, Department of Chemistry, 2012)
This thesis presents the development of chlorophyll, cholic acid, aflatoxin B1 molecularly imprinted polymer (MIP) particles and cholic acid MIP nanofibers for application as selective solid phase extraction (SPE) sorbents. The particles were prepared by bulk polymerization and the nanofibers by a novel approach combining molecular imprinting and electrospinning technology. The AFB1 MIP particles were compared with an aflatoxin specific immunoextraction sorbent in cleaning-up and pre-concentrating aflatoxins from nut extracts. They both recorded high extraction efficiencies (EEs) of > 97 % in selectively extracting the aflatoxins (AFB1, AFB2, AFG1 and AFG2). High reproducibility marked by the low %RSDs of < 1% and low LODs of ≤ 0.02 ng/g were calculated in all cases. The LODs were within the monitoring requirements of the European Commission. The results were validated with a peanut butter certified reference material. The chlorophyll MIP on the other hand selectively removed chlorophyll that would otherwise interfere during pesticide residue analysis (PRA) from > 0.6 to <0.09 Au in green plants extracts. The extracted chlorophyll was removed to far below the level of ≥ 0.399 Au that is usually associated with interference during PRA. Furthermore, the MIP demonstrated better selectivity by removing only chlorophyll (> 99%) in the presence of planar pesticides than the currently employed graphitized carbon black (GCB) that removed both the chlorophyll (> 88%) and planar pesticides (> 89%). For the interfering cholic acid during drug residue analysis, cholic acid MIP electrospun nanofibers demonstrated to be more sensitive and possessing higher loading capacity than the MIP particles. 100% cholic acid was removed by the nanofibers from standard solutions relative to 80% by the particles. This showed that the nanofibers have better performance than the micro particles and as such have potential to replace the particle based SPE sorbents that are currently in use. All the templates were optimally removed from the prepared MIPs by employing a novel pressurized hot water extraction template removal method that was used for the first time in this thesis. The method employed only water, an environmentally friendly solvent to remove templates to ≥ 99.6% with template residual bleeding of ≤ 0.02%.
Keywords: Sorbents -- Research Nanofibers -- Research Aflatoxins -- Research Electrospinning -- Research Extraction (Chemistry) -- Research